Impact of plug-in electric vehicles on voltage imbalance in distribution system - Somticha Panich; Singh, Jai Govind; Weerakorn Ongsakul; Dhakal, Shobhakar; PEA; Asian Institute of Technology Education Cooperation Project (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Plug-in electric vehicle (PEV) will soon be connected to residential distribution networks. They are considered as huge residential loads when being charged. However as the battery technology improves, they will also be able to support the network as small dispersed generation units which transfer the energy stored in their battery into grid. Even though the PEV connection gradually increases, their connection points and charging/discharging levels randomly vary. Therefore, such single - phase bi - directional power flow can have adverse effect on the voltage unbalance of a three - phase distribution network. In this paper, impact of plug - in electric vehicles on voltage imbalance in distribution system is presented. In G2V mode, the voltage unbalance analysis is carried out five variations including penetration levels, PEVs connected location, PEV models that have different charging rate, and charging period. Meanwhile, the five variations are also involved in V2G mode analysis. Additionally, the voltage unbalance due to PEVs discharging and other types of distribution generator as photovoltaic and wind turbines are compared. Finally, some voltage unbalance mitigation techniques are summarized.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2014
Keywords: Electric vehicles -- Energy consumption; Battery chargers